2019
DOI: 10.3390/diseases7010029
|View full text |Cite
|
Sign up to set email alerts
|

Keeping an Eye on Perimenopausal and Postmenopausal Endometriosis

Abstract: Introduction: We aimed to describe and review the epidemiological aspect of the disease pattern of a series of perimenopausal and postmenopausal women with a histology confirmation of endometriosis. Material and Methods: We retrospectively examined the clinical records of 184 perimenopausal and 46 postmenopausal women with endometriosis. Data were collected and analyzed from 1100 patients’ charts with confirmed endometriosis and involved cases from two different geographical areas, New Haven (US) and Greece. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…It was found that endometrioma and uterine leiomyoma were the most common condition among women with perimenopausal endometriosis compared to the postmenopausal group and adenomyosis was found to be higher in postmenopausal patients. In both the groups, endometriosis-associated ovarian cancer and uterine cancer were similar (Table 2) [34].…”
Section: Perimenopausal and Postmenopausal Effectsmentioning
confidence: 79%
“…It was found that endometrioma and uterine leiomyoma were the most common condition among women with perimenopausal endometriosis compared to the postmenopausal group and adenomyosis was found to be higher in postmenopausal patients. In both the groups, endometriosis-associated ovarian cancer and uterine cancer were similar (Table 2) [34].…”
Section: Perimenopausal and Postmenopausal Effectsmentioning
confidence: 79%
“…The literature on the subject increasingly emphasizes the issue of endometriosis in the perimenopausal period. It is a severe disease, which is increasingly occurring and has serious long-term health consequences, including a negative impact on the women’s quality of life and functioning [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A third theory involves lymphovascular spread which explains cases in which hepatic endometriomas are only intraparenchymal [126]. A last theory is that of survival of the intrahepatic Mullerian rest: the Mullerian structures believed to be in the hepatic parenchyma maintain their functional potential, even surviving the long hormonal silence between the fall of placental hormones and the onset of puberty [127,128]. As regards the rare cases of postmenopausal HE, it is thought [128] that they may be linked to the reactivation of endometrial implants following the administration of hormone replacement therapy in patients with previous history of endometriosis.…”
Section: Hepatic Endometriosismentioning
confidence: 99%